Reasoning in the tradition of Arabic grammar: History and manifestations - Al-Dosari, Musfir bin Mahmas (Research Journal in Advanced Humanities, 2025)
Reasoning (ta‘līl) has been a cornerstone in the development of Arabic grammar, significantly shaping its theoretical foundations and analytical methodologies. This study traces the historical evolution of reasoning in the Arabic grammatical tradition, examining its origins, key influences, and major transformations. It explores how classical grammarians justified linguistic rules, identified underlying linguistic patterns, and provided logical explanations for grammatical structures. Additionally, the research investigates the different manifestations of reasoning in syntactic, morphological, and phonological analyses. By highlighting the role of reasoning in Arabic grammar, this study underscores its impact on linguistic thought and its continued relevance to contemporary linguistic research.